Calibration of the logarithmic-periodic dipole antenna (LPDA) radio stations at the Pierre Auger Observatory using an octocopter. (16th October 2017) - Aab, A.; Abreu, P.; Aglietta, M.; Samarai, I. Al; Albuquerque, I.F.M.; Allekotte, I.; Almela, A.; Castillo, J. Alvarez; Alvarez-Muñiz, J.; Anastasi, G.A.; Anchordoqui, L.; Andrada, B.; et al.
Abstract: An in-situ calibration of a logarithmic periodic dipole antenna with a frequency coverage of 30 MHz to 80 MHz is performed. Such antennas are part of a radio station system used for detection of cosmic ray induced air showers at the Engineering Radio Array of the Pierre Auger Observatory, the so-called Auger Engineering Radio Array (AERA) . The directional and frequency characteristics of the broadband antenna are investigated using a remotely piloted aircraft carrying a small transmitting antenna. The antenna sensitivity is described by the vector effective length relating the measured voltage with the electric-field components perpendicular to the incoming signal direction. The horizontal and meridional components are determined with an overall uncertainty of7.4^+0.9_-0.3% 7.4 +0.9 −0.3 % and10.3^+2.8_-1.7% 10.3 +2.8 −1.7 % respectively. The measurement is used to correct a simulated response of the frequency and directional response of the antenna. In addition, the influence of the ground conductivity and permittivity on the antenna response is simulated. Both have a negligible influence given the ground conditions measured at the detector site. The overall uncertainties of the vector effective length components result in an uncertainty of8.8^+2.1_-1.3% 8.8 +2.1 −1.3 % in the square root of the energy fluence for incoming signal directions with zenith angles smaller than60^° 60° .